Acupuncture Rescues Cognitive Impairment and Upregulates Dopamine-β-Hydroxylase Expression in Chronic Cerebral Hypoperfusion Rats. (12th July 2018) - Xiao, Ling-Yong; Yang, Jing-Wen; Wang, Xue-Rui; Ye, Yang; Yang, Na-Na; Yan, Chao-Qun; Liu, Cun-Zhi
Abstract : Alteration of dopamine (DA) and noradrenaline (NA) contributes to cognitive function. Acupuncture has been shown to affect DA and NA in chronic cerebral hypoperfusion (CCH) rats. However, the effect of acupuncture on DA- β -hydroxylase (DBH), the biosynthetic enzyme of NA, remains unknown. In CCH rats we established chronic hypoperfusion by bilateral common carotid artery occlusion (two-vessel occlusion, 2VO) and treated them with acupuncture. Acupuncture displayed beneficial effects on hippocampus-dependent memory impairments, including nonspatial and spatial memory. That is also reflected in hippocampus long-term-potentiation (LTP). Moreover, DBH expression in the hippocampus and DBH activity in cerebrospinal fluid were upregulated after acupuncture treatment. In conclusion, these in vivo findings suggest that acupuncture exerts a therapeutic effect on hippocampus-dependent memory and hippocampus LTP in CCH rats, which may be partially related to the modulation of DBH in the hippocampus.